SUPPORTING ADDITIVE MANUFACTURING TECHNOLOGY DEVELOPMENT THROUGH CONSTRAINT MODELLING IN EARLY CONCEPTUAL DESIGN: A SATELLITE PROPULSION CASE STUDY. (May 2020) - Borgue, O.; Valjak, F.; Panarotto, M.; Isaksson, O.
Abstract: Function and constraints modelling are implemented to design two gridded ion thrusters for additive manufacturing (AM). One concept takes advantage of AM design freedom, disregarding AM limitations and is not feasible. The other concept considers AM limitations and is manufacturable and feasible. Constraints modelling highlights AM capabilities that can be improved, showing where future investment is needed. Constraints representation can also support the creation of technology development roadmaps able to identify areas of AM technologies that must be improved.